Evaluation of the in vitro efficacy of hemodialysis, hemoperfusion, and the combined approach on the removal of metaldehyde from canine plasma. Issue 4 (24th May 2016) - Mauser, Elisabeth L.; Puschner, Birgit; Reese, Sven; Hartmann, Katrin; Doerfelt, René
Abstract: Objective: To evaluate the effect of hemodialysis, hemoperfusion, and a combined approach on the removal of metaldehyde from canine plasma. Design: In vitro study. Setting: University veterinary teaching hospital laboratory. Animals: None. Interventions: None. Measurements and Main Results: Metaldehyde‐fortified canine plasma was prepared. Hemodialysis (HD), charcoal hemoperfusion (HP), and in‐series hemodialysis and charcoal hemoperfusion (HD/HP) were applied in triplicate to eliminate metaldehyde from plasma. Plasma samples were obtained before starting the procedure and subsequently after every processed total plasma volume until plasma had been processed 10 times. Plasma metaldehyde concentration was quantitatively assayed by gas chromatography‐mass spectrometry. Statistical analysis was performed using one‐way ANOVA, repeated measures ANOVA, and Bonferroni post hoc test, and by calculating the coefficient of variation from duplicate measurements, binomial distribution, and by Bland–Altman analysis. Statistically significant reduction in metaldehyde concentration was reached by all 3 techniques. Reduction of metaldehyde concentration of more than 95% was achieved after processing the plasma volume 4 times applying HD, 8 times applying HP, and 2 times applying HD/HP. Efficacy in reduction of metaldehyde concentration differed significantly between the 3 procedures ( P < 0.001). In‐series hemodialysis and charcoal hemoperfusion was more effective in metaldehyde removal than HD ( P = 0.003) and HP ( P < 0.001), and HD was more effective than HP ( P = 0.002). Conclusions: Metaldehyde was effectively removed by all applied extracorporeal blood purification techniques in vitro. However, the combination of both techniques was more effective than HD or HP alone. Further clinical studies are warranted to confirm therapeutic benefits in patients.